2020
DOI: 10.1002/cam4.2827
|View full text |Cite
|
Sign up to set email alerts
|

Daratumumab prevents programmed death ligand‐1 expression on antigen‐presenting cells in de novo multiple myeloma

Abstract: Background Daratumumab (Dara), an anti‐CD38 monoclonal antibody, has an immunologic mechanism of action through targeting of CD38 expressing immune cells in patients with multiple myeloma (MM). Furthermore, it was recently shown that CD38 upregulation in tumors, is a major mechanism of acquired resistance to antiprogrammed cell death 1 (PD‐1)/programmed cell death ligand 1 (PD‐L1). Therefore, we decided to evaluate the immunomodulatory effects of CD38 blockade by Dara on the PD‐L1 expressing immune cells. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…Other immune effector cells also show high expression of CD38 including regulatory B cells and antigen presenting cells (APC), especially plasmacytoid dendritic cells. A decrease in plasmacytoid densdritic cells, which support MM cell growth and survival, may represent another potent immune effect of CD38 antibodies [ 5 , 6 ]. CD38 works as an enzyme (ectoenzyme) at it also can serve as a receptor triggering proliferation signals [ 7 ].…”
Section: Cd38mentioning
confidence: 99%
“…Other immune effector cells also show high expression of CD38 including regulatory B cells and antigen presenting cells (APC), especially plasmacytoid dendritic cells. A decrease in plasmacytoid densdritic cells, which support MM cell growth and survival, may represent another potent immune effect of CD38 antibodies [ 5 , 6 ]. CD38 works as an enzyme (ectoenzyme) at it also can serve as a receptor triggering proliferation signals [ 7 ].…”
Section: Cd38mentioning
confidence: 99%
“…Interestingly, a study detailing acute Ebola infection of humans similarly found that CD38 upregulation on pDCs was correlated to declining viral load (48), suggesting that pDC CD38's role in viral infections may be broader than just influenza. The relevance of CD38 on pDCs is further underscored by a report that the CD38-targeted therapeutic daratumumab (63), approved for the treatment of multiple myeloma, depletes circulating pDCs (64). Strategies for the modulation of pDC CD38 may warrant investigation as potential therapies for viral infections or autoimmune diseases associated with dysregulated overaction of pDC IFN-I production.…”
Section: Virus Challengementioning
confidence: 99%
“…CD38/ADO and PD-1/PD-L1 axis in cancers; however, this approach has not been explored in depth in MM patients. Interestingly, it has been reported that the treatment with anti-CD38 mAb daratumumab (DARA) prevents the increase of PD-L1 expression on antigen presenting cells induced by the standard treatment without DARA in MM patients [95]. Moreover, it has been showed that MM cells increase PD-1 expression by NK and PD-L1 by monocytes and that PD-1/PD-L1 axis suppress the antibody-dependent cellular cytotoxicity (ADCC) mediated by the anti-CD38 mAb isatuximab [96].…”
Section: The Possible Link Between Cd38 and Pd-l1 In MMmentioning
confidence: 99%